Waste pickers in the informal economy of the Global South: included or excluded?. Issue 5 (13th June 2017) - Coletto, Diego; Bisschop, Lieselot
Abstract : Purpose: The purpose of this paper is to provide insights into the role and practices of informal waste pickers and the implications for waste management policy in urban contexts of the Global South. Design/methodology/approach: Qualitative case studies were used, including interviews, observations and document analyses. The authors compared informal waste management in two cities of the Global South: Accra (Ghana) and Porto Alegre (Brazil). Findings: The analysis points out that informal waste pickers play a crucial role in the implementation of waste policies in both cities, despite differing economic, social and institutional contexts. The study of the waste management system also points to multiple connections between informal and formal parts of the economy. Although the informal waste pickers are integral to the waste management systems, their economically disadvantaged position excludes them from the formal labour market. Faced with these challenges, they develop creative solutions to guarantee their livelihood and gain more effective collective voice. Research limitations/implications: The comparison of two case studies, conducted about the same social phenomenon in two different economic, institutional and social contexts, has limited generalisability but is theoretically and practically important. Practical implications: The findings are relevant to policy-makers who deal with urban waste management and for organisations who develop support actions for informal workers. Originality/value: The authors draw on a comparison of qualitative case studies to explore the multidimensionality of the waste picker's phenomenon. This paper sparks discussion among scholars and experts who study the informal economy from different perspectives, in this case bridging insights from sociology and victimology.